1952
DOI: 10.1001/archneurpsyc.1952.02320170079011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electroencephalographic Effects of Prefrontal Lobotomy and Topectomy in Chronic Psychoses

Abstract: Case Material and Procedures.\p=m-\Withthe exception of one patient with manic-depressive psychosis, all had chronic advanced schizophrenia of paranoid, hebephrenic, or catatonic type. A comparative study of the effects of prefrontal lobotomy and topectomy seemed to be particularly applicable in a rather homogeneous group of patients with advanced schizophrenia.A selection of the patients for one or the other procedure was deliberately avoided. All 105 patients\p=m-\84 from the Northport Veterans Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1957
1957
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…and inhibition of spindle activity in the sleep EEG., the site of action of butaperazine and other piperazine-phenothiazines was also postulated to be on the reticular formation at brainstem level (1, 13). Since studies in man and animals have shown that the frontal lobotomy operation may result in thalamocortical dysfunction and thalamic degeneration (8,10,18,19,21,24,25), in our case, the functional interaction between thalamus, basal ganglia, and reticular formation was already disturbed by possible degenerative changes in the thalamus. It would seem reasonable to suggest, therefore, that the episodes of akinetic mutism were associated with drug-induced functional alterations in the reticular formation at brainstem or thalamic level as a result of thalamic dysfunction.…”
Section: Discussionmentioning
confidence: 54%
“…and inhibition of spindle activity in the sleep EEG., the site of action of butaperazine and other piperazine-phenothiazines was also postulated to be on the reticular formation at brainstem level (1, 13). Since studies in man and animals have shown that the frontal lobotomy operation may result in thalamocortical dysfunction and thalamic degeneration (8,10,18,19,21,24,25), in our case, the functional interaction between thalamus, basal ganglia, and reticular formation was already disturbed by possible degenerative changes in the thalamus. It would seem reasonable to suggest, therefore, that the episodes of akinetic mutism were associated with drug-induced functional alterations in the reticular formation at brainstem or thalamic level as a result of thalamic dysfunction.…”
Section: Discussionmentioning
confidence: 54%
“…The ipsilateral spindle depression following unilateral frontal leucotomy was first observed [125][126]. Cress and Gibbs (1948) observed spindle asymmetries (ipsilateral depression) in 98 % of patients with hemispheric cerebrovascular accidents, whereas only 48% had focal abnormalities in the waking EEG [127].…”
Section: Sleep the Distribution Of Spindles Recovery After Strokementioning
confidence: 99%
“…Spindle distribution may be locally depressed by various types of cortical, subcritical pathology, including the generation of ascending reticular formation and thalamo-cortical pathways. The ipsilateral spindle depression following unilateral frontal leucotomy was first observed [125][126]. Cress and Gibbs (1948) observed spindle asymmetries (ipsilateral depression) in 98 % of patients with hemispheric cerebrovascular accidents, whereas only 48% had focal abnormalities in the waking EEG [127].…”
Section: Sleep the Distribution Of Spindles Recovery After Strokementioning
confidence: 99%